Exploring genetic variation in the tomato (Solanum section Lycopersicon) clade by whole‐genome sequencing. (3rd September 2014) - The 100 Tomato Genome Sequencing Consortium; Aflitos, Saulo; Schijlen, Elio; de Jong, Hans; de Ridder, Dick; Smit, Sandra; Finkers, Richard; Wang, Jun; Zhang, Gengyun; Li, Ning; Mao, Likai; Bakker, Freek; et al.
Summary We explored genetic variation by sequencing a selection of 84 tomato accessions and related wild species representative of the Lycopersicon, Arcanum, Eriopersicon and Neolycopersicon groups, which has yielded a huge amount of precious data on sequence diversity in the tomato clade. Three new reference genomes were reconstructed to support our comparative genome analyses. Comparative sequence alignment revealed group‐, species‐ and accession‐specific polymorphisms, explaining characteristic fruit traits and growth habits in the various cultivars. Using gene models from the annotated Heinz 1706 reference genome, we observed differences in the ratio between non‐synonymous and synonymous SNPs (dN/dS) in fruit diversification and plant growth genes compared to a random set of genes, indicating positive selection and differences in selection pressure between crop accessions and wild species. In wild species, the number of single‐nucleotide polymorphisms (SNPs) exceeds 10 million, i.e. 20‐fold higher than found in most of the crop accessions, indicating dramatic genetic erosion of crop and heirloom tomatoes. In addition, the highest levels of heterozygosity were found for allogamous self‐incompatible wild species, while facultative and autogamous self‐compatible species display a lower heterozygosity level. Using whole‐genome SNP information for maximum‐likelihood analysis, we achieved complete tree resolution, whereas maximum‐likelihood trees based on SNPs from ten fruit and growth genes show incomplete resolution for the crop accessions, partly due to the effect of heterozygous SNPs. Finally, results suggest that phylogenetic relationships are correlated with habitat, indicating the occurrence of geographical races within these groups, which is of practical importance for Solanum genome evolution studies.